Early Birds in Day Care: The Social Gradient in Starting Day Care and Children's Non-cognitive Skills - Frauke H. Peter; Pia S. Schober; Katharina C. Spiess (CESifo Economic Studies, 2016)
In recent years, almost all children below school age in Western industrialized countries have some experience of attending day care institutions. However, the age at which children enter day care and therefore the overall time spent in day care varies substantially. We investigate the potential impact of later day care entry on the social and emotional behaviour of children, one important aspect of non-cognitive skills. Based on the English sample of the Millennium Cohort Study, we analyse how later entries are associated with children's development at the age of 5 and 7 years, using propensity score techniques. We find clear evidence of significant associations at the age of 7 years: Later day care entry appears to increase children's peer problems and to reduce prosocial behaviour. We find hardly any associations with the emotional development of children. Children with low-educated mothers and those from families with a household income below the poverty line are most strongly affected, which provides support for a social gradient in how earlier day care entry impacts non-cognitive skills.
Keywords: J13; I21; 330